The Effect of Job Stress on Employee Enthusiasm A Sample of Banks: Sinnar Locality-2021 - د. أبوبكر علي خضر بخيت (White Nile Journal for Studies and Research, 2022)
The study aimed to find out the effect of job stress in its dimensions (psychological exhaustion, personal achievement, personel relationship) on the employees' enthusiasm in its dimensions (effort at work, abilities and characteristics, individual's awareness of his job role). A random sample was selected from bank employees - Sennar locality - Sennar state, using a questionnaire tool to collect data. The descriptive analytical approach was used for the data using the Statistical Package for Social Sciences (SPSS). The results revealed: There is a statistically significant relationship at the level of significance (0.05) between job stress with its dimensions (psychological exhaustion, personal achievement personel relationship) on employee enthusiasm in two dimensions (effort at work, Abilities and characteristics, the individual's perception of his job role) There is a statistical relationship at the level of significance (0.05) between (psychological exhaustion) and (effort at work) There is no statistical relationship at the level of significance (0.05) between (psychological exhaustion, personel relationship) And (the individual's awareness of his job role) The most important recommendations: It was recommended that the training programs include some behavior change skills, improve the system of material and moral incentives, and pay attention to the internal work environment.